2017
DOI: 10.1074/jbc.m117.811646
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint kinase 1–induced phosphorylation of O-linked β-N-acetylglucosamine transferase regulates the intermediate filament network during cytokinesis

Abstract: Checkpoint kinase 1 (Chk1) is a kinase instrumental for orchestrating DNA replication, DNA damage checkpoints, the spindle assembly checkpoint, and cytokinesis. Despite Chk1's pivotal role in multiple cellular processes, many of its substrates remain elusive. Here, we identified linked β--acetylglucosamine (-GlcNAc)-transferase (OGT) as one of Chk1's substrates. We found that Chk1 interacts with and phosphorylates OGT at Ser-20, which not only stabilizes OGT, but also is required for cytokinesis. Phospho-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 30 publications
3
47
0
Order By: Relevance
“…Vimentin phosphorylation regulates a number of cellular functions. For example, Ser71 phosphorylation was reported to stimulate vimentin filament formation during cytokinesis [59] . The NEDD9 paralog, p130Cas, was reported to be a vimentin interacting protein that is displaced from vimentin upon phosphorylation of Ser56 [46] , [47] .…”
Section: Discussionmentioning
confidence: 99%
“…Vimentin phosphorylation regulates a number of cellular functions. For example, Ser71 phosphorylation was reported to stimulate vimentin filament formation during cytokinesis [59] . The NEDD9 paralog, p130Cas, was reported to be a vimentin interacting protein that is displaced from vimentin upon phosphorylation of Ser56 [46] , [47] .…”
Section: Discussionmentioning
confidence: 99%
“…Chk1 inhibition by the small‐molecule inhibitor UCN‐01 does not reduce Aurora B‐S331 phosphorylation at the midbody compared with control cells, indicating that Chk1 does not regulate abscission through Aurora B‐S331 phosphorylation; instead, the Cdc‐like kinases 1, 2, and 4 are required for Aurora B‐S331 phosphorylation and complete Aurora B activation in late cytokinesis . Because Chk1‐deficient HeLa cells exhibit increased frequency of intermediate filament (vimentin) bridges compared with controls in late cytokinesis , one possibility is that Chk1 prevents furrow regression by promoting vimentin severing through an incompletely understood mechanism (Fig. A).…”
Section: Dna Damage Response Proteins In Cytokinesismentioning
confidence: 99%
“…Kaasik et al [82] showed that GSK3b can phosphorylate OGT at Ser3 and/or Ser4, whereby these phosphorylations enhance OGT activity. Recently, Li et al [83] showed that Checkpoint kinase 1 can phosphorylate OGT on Ser20, which seemingly improves OGT stability. In addition, AMPK was found to phosphorylate OGT on Thr444, which induced changes in OGT substrate specificity [34,84].…”
Section: Phosphorylation/o-glcnacylation Crosstalk At the Enzyme Levelmentioning
confidence: 99%